An empirical study of determinants of market response to initial operational loss events disclosure: Evidence from US bank and non-bank financial institutions - Yibo, Wang (2015)
This dissertation investigates the determinants of impact of operational risk events on the stock market behaviour of affected US bank and non-bank financial insitutions over period from 2010:Q1 to 2014:4. Firstly, I conduct event study methodology to estimate abnormal market returns of affected banks and non-bank financial institutions. Secondly, I employ Imbierowicz and Rauch’s (2014) proxy for credit risk and liquidity risk for banks. Besides, I use credit rating as additional credit risk proxy for both banks and non-bank financial firms. Cross-sectional regression is made on the CAAR and these proxies as well as control variables. I find that for US non-bank events, market reaction is negatively correlated with credit risk and negatively correlated with liquidity risk. For US bank events, there is no relationship between Z-score and CAAR for entire bank events; cumulative abnormal return is negatively correlated with credit risk, upgrade and bank size before event date while it is positively correlated with liquidity risk and downgrade before event date. For US median and large banks I observe positive correlation between them in median and large banks. Possible explanations are provided.